Isolation and characterization of beneficial bacteria from Apis Cerana honeybees from Hanoi, Vietnam - Quyen, Dong Van; Lanh, Pham Thi; Ha Thi Thu, (Vietnam Journal of Biotechnology, 2024)
Beneficial bacteria are vital for maintaining honeybee health by outcompeting pathogenic microorganisms, boosting immunity, and enhancing resilience to diseases. Identifying the specific bacterial strains associated with honeybees enables the development of targeted probiotics that can improve the health of bees and humans. The present study describes the isolation and identification of bacterial strains from Apis cerana honeybees in Hanoi, Vietnam, utilizing a culture-based method, Matrix-Assisted Laser Desorption-Ionization Time of Flight Mass Spectrometry (MALDI-TOF) analysis, and 16S rRNA sequencing. MALDI-TOF analysis revealed several beneficial bacterial species, including Lactobacillus kunkeei, Lactobacillus plantarum, Pediococcus pentosaceus, Leuconostoc mesenteroides, Leuconostoc citreum, Bacillus subtilis, and Bacillus megaterium. Antimicrobial spectrum analysis showed that 16 out of the 23 identified isolates exhibited inhibitory effects against tested bacteria. Selected isolates with broad antimicrobial spectra, including L. kunkeei, L. plantarum, P. pentosaceus, L. mesenteroides, L. citreum, and B. subtilis, were further validated through 16S rRNA gene sequencing. The results confirmed the identity of these strains, emphasizing the probiotic potential of L. kunkeei, L. plantarum, L. mesenteroides, L. citreum, P. pentosaceus, and B. subtilis for honeybee health. Our findings provide valuable insights into the bacterial diversity and antimicrobial properties associated with honeybees, suggesting their use as probiotics in beekeeping and beyond.